Compliance to the agreement on technical barrier to trade (TBT): the case of Malaysia’s environmental protection measures - Yanti Ahmad Shafiee; Caroline Rosie Jeffrey Nasah; Fithriah Ab Rahim (Human Resource Management Academic Research Society (HRMARS), 2025)
This article examines the impact of Trade-Related Environmental Measures (TREMs) on Malaysia, with a specific focus on the Technical Barriers to Trade (TBT) Agreement under the World Trade Organization (WTO) framework. As international trade increasingly incorporates environmental standards, developing countries like Malaysia face unique challenges and opportunities in balancing trade liberalization with environmental sustainability. The articles explore how TREMs imposed by major trading partners affect Malaysia’s import and export sectors, particularly in industries sensitive to environmental regulations such as palm oil, electronics, and manufacturing. Through an analysis of key WTO disputes, domestic regulatory adjustments, and the WTO trade agreements, this article assesses the effectiveness of Malaysia’s compliance with the TBT Agreement and its application of the domestic regulations, while highlighting potential barriers and benefits. The findings suggest that while TREMs can drive improvements in environmental standards, they may also impose additional costs and technical challenges on Malaysia’s imports and exports, necessitating enhanced regulatory capacity and international cooperation.